Preclinical evaluation of alternatives to oral immunotherapy for food allergies - Johnson-Weaver, Brandi T. (Frontiers in Allergy, 2023)
The increasing food allergy incidence has led to significant interest in developing therapies for allergic diseases. Oral allergen-specific immunotherapy (OIT) is a recently FDA-approved therapeutic to treat peanut allergies. OIT utilizes daily allergen dosing to reduce allergic reactions to peanuts. However, there is diminished enthusiasm for daily OIT, potentially due to the strict regimen required to induce desensitization and the risks of severe adverse events. Thus, there remains a need for safe and effective food allergy treatments that are well-received by allergic individuals. Preclinical research studies investigate methods to induce allergen desensitization in animals and support clinical studies that address the limitations of current food allergy OIT. Because allergic reactions are triggered by allergen doses above an individual's activation threshold, immunotherapy regimens that induce allergen desensitization with lower allergen doses or without the requirement of daily administrations may expand the use of food allergy immunotherapy. Administering allergen immunotherapy by alternative routes is a strategy to induce desensitization using lower allergen doses than OIT. Several animal models have evaluated oral, sublingual, epicutaneous, and intranasal immunotherapy routes to treat food allergies. Each immunotherapy route may require different allergen doses, formulations, and treatment schedules to induce desensitization. This article will discuss scientific findings from food allergy immunotherapy animal studies that utilize various immunotherapy routes to induce allergen desensitization to support future clinical studies that enhance the safety and efficacy of allergen immunotherapy to treat food allergies.